Excess electron transport in cryoobjects - Eshchenko, D.G.; Storchak, V.G.; Brewer, J.H.; Cottrell, S.P.; Cox, S.F.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Experimental results on excess electron transport in solid and liquid phases of Ne, Ar, and solid N2-Ar mixture are presented and compared with those for He. Muon spin relaxation technique in frequently switching electric fields was used to study the phenomenon of delayed muonium formation: excess electrons liberated in the m+ ionization track converge upon the positive muons and form Mu (m+e-) atoms. This process is shown to be crucially dependent upon the electron`s interaction with its environment (i.e., whether it occupies the conduction band or becomes localized in a bubble of tens of angstroms in radius) and upon its mobility in these states. The characteristic lengths involved are 10-6-10-4 cm, the characteristic times range from nanoseconds to tens microseconds.Such a microscopic length scale sometimes enables the electron spend its entire free lifetime in a state which may not be detected by conventional macroscopic techniques. The electrontransport processes are compared in: liquid and solid helium (where electron is localized in buble); liquid and solid neon (where electrons are delocalized in solid and the coexistence of localized anddelocalized electrons states was found in liquid recently); liquid and solid argon (where electrons are delocalized in both phases); orientational glass systems (solid N2-Ar mixtures), where our results suggest that electrons are localized in orientational glass. This scaling from light to heavy rare gases enables us to reveal new features of excess electron localization on microscopic scale. Analysis of the experimental data makes it possible to formulate the following tendency of themuon end-of-track structure in condensed rare gases. The muon-self track interaction changes from the isolated pair (muon plus the nearest track electron) in helium to multi-pair (muon in the vicinity of tens track electrons and positive ions) in argon.